DESIGN OF A CREATIVE WOMEN'S COLLECTION USING THE SOURCE OF INSPIRATION «UKRAINIAN TOWEL» - Яценко, М. В.; Кернеш, В. П.; Бунтовська, А. В.; Омельченко, Г. В. (Fashion Industry, 2023)
Purpose. Design-projection of a stylized ethnic collection of clothes and shoes using motifs of craft embroidery of the Ukrainian people. Methodology. The article uses the method of synthesis and analysis of scientific and technical documentation according to the direction of research. Based on the results of the conducted research by the method of synthesis, new original solutions for the components of the creative collection of women's clothing and footwear were obtained. The application of the methods of graphic transformation and morphological analysis made it possible to present the shape, texture, decorative elements and color scheme of the future creative collection. Results. To achieve the goal, modern design methods and tools of graphic computer programs were used in the work to solve the following problems: the creative source of inspiration "Ukrainian towel" was visualized, morphological analysis and typification of the elements of craft embroidery patterns of Ukrainian towels of the Volyn region were carried out, elements of clothing in ethnic style were analyzed, typified its main characteristic features (shape, color range, structural and decorative details and decoration), developed new forms of clothing and footwear in the proposed artistic and design solution of the modern collection. Scientific novelty in obtaining newly synthesized elements of modern clothing in ethnic style based on the use of Ukrainian ethnic motifs. Practical value. The practical significance of the work consists in obtaining typified elements that can be used as a basis for the synthesis of new original constructive and technological solutions. Newly synthesized elements of modern clothing in ethnic style based on the use of Ukrainian ethnic motifs were obtained. A line of sketches of women's clothing and shoes was developed using elements of transformation, which includes isolated elements of Ukrainian embroidery in combination with a stylized form of ethnic motifs. The use of elements of national embroidery in modern collections demonstrates to the world public a traditional, unique, recognizable image and a sense of Ukrainian identity and belonging to the historical heritage of Ukraine.